1994
DOI: 10.1111/j.1532-5415.1994.tb07484.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Disease and Function and Perceived Health in Very Frail Elders

Abstract: Disease, observed function, and self-perceived health status are separate, but interrelated entities, with disease having a stronger relationship to observed function than self-perceived health. Comprehensive assessment of frail elders may need to include all three areas, and studies that focus on one area should take into account the other two as potential important covariates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 29 publications
2
52
1
Order By: Relevance
“…This finding seems in contrast with the notion that nursing home residents typically have multiple functional dependencies and frequent comorbid conditions [35], and it disagrees with previous findings in different settings. For example, Van Dijk et al [39], examining specifically nursing home residents with dementia, found they had more comorbidity relative to patients less cognitively impaired.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding seems in contrast with the notion that nursing home residents typically have multiple functional dependencies and frequent comorbid conditions [35], and it disagrees with previous findings in different settings. For example, Van Dijk et al [39], examining specifically nursing home residents with dementia, found they had more comorbidity relative to patients less cognitively impaired.…”
Section: Discussioncontrasting
confidence: 56%
“…Among patients diagnosed with dementia, functional status seems to relate to the severity of cognitive impairment, regardless of coexistent diseases [32][33][34]. On the other hand, despite etiology encompassing social, behavioral and environmental factors [35][36][37], the most important determinant of functional status remains the presence of comorbidity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Disability was measured using the subscale somatic autonomy (17 items concerning perceived physical functioning) of the Dutch version of the Sickness Impact Profile (SIP) (De Bruin, 1996). The SIP was developed for patients with chronic diseases and is also used in nursing home populations (Rothman et al, 1989;Gerety et al, 1994;Mulrow et al, 1994). Cronbach's alpha of the Dutch version of the subscale somatic autonomy was 0.85 (Van Campen and Kerkstra, 1998).…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Identification of medical conditions associated with the most functional limitations would enable more accurate estimates of the potential benefits of intervention or disease prevention methods. In recent years, population studies have examined different aspects of the relationship between diseases and disability in the community (1-4) as well as in nursing homes (5). Some are crosssectional studies, which only examine associations, while longitudinal studies will identify predisposing factors.…”
mentioning
confidence: 99%